AN ANALYSIS OF CODE SWITCHING IN BILINGUAL SCHOOL IN COMMUNICATION BY NON-NATIVE SPEAKER ENGLISH TEACHER IN BALI - Zee, Zenitha (Jurnal Pendidikan Bahasa Inggris Indonesia, 2020)
Abstract This study aimed at investigating types of code-switching pattern which used by non-native speaker English teacher and the reason to use the code-switching. This research was a descriptive qualitative research. There were 3 informant samples from non native speaker English speaker in a bilingual school in Bali. The data were collected by using observation and interview. The results showed that, 1) there is an indication of insertion and alternation which occurred by non native speaker English during communication and mostly in the form of simple imperative and instructional utterances, and 2) the reason to use the code switching is to introduce the students the habit of using English